2002
DOI: 10.1086/339205
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microsporidiosis Due toEnterocytozoon bieneusiin Elderly Human Immunodeficiency Virus–Negative Patients from Vigo, Spain

Abstract: We report what is, to our knowledge, the first study in which microsporidial infection was detected in elderly human immunodeficiency virus (HIV)--negative patients. Of the 60 elderly patients studied, 47 had diarrhea. Intestinal microsporidiosis due to Enterocytozoon bieneusi was diagnosed in 8 patients (17.02%) by use of Weber's chromotrope-based stain and polymerase chain reaction with species-specific primers. The mean age of these 8 patients was 75 years; 7 had chronic diarrhea and 1 had nonchronic diarrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
4
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 19 publications
4
71
4
2
Order By: Relevance
“…The first suggestion that microsporidia are associated with human infections was made in 1924, and up to 1985, there were less than a dozen reports of human microsporidiosis (Wittner and Weiss, 1999). Since 1985 with the recognition that Enterocytozoon bieneusi causes diarrhoea in patients with AIDS (Desportes et al, 1985), many infections with different species of microsporidia have been reported from all over the world and microsporidia are now frequently recognised as etiologic agents of opportunistic infections in persons with AIDS, and more recently, in organ transplant recipients, patients being treated with immunosuppressive drugs and immunocompetent patients (Weber and Bryan, 1994;Sax et al, 1995;Wanke et al, 1996;Bryan et al, 1997;Raynaud et al, 1998;Gumbo et al, 1999;Wittner and Weiss, 1999;Metge et al, 2000;Lores et al, 2002;Lewis et al, 2003).…”
Section: Overviewmentioning
confidence: 99%
“…The first suggestion that microsporidia are associated with human infections was made in 1924, and up to 1985, there were less than a dozen reports of human microsporidiosis (Wittner and Weiss, 1999). Since 1985 with the recognition that Enterocytozoon bieneusi causes diarrhoea in patients with AIDS (Desportes et al, 1985), many infections with different species of microsporidia have been reported from all over the world and microsporidia are now frequently recognised as etiologic agents of opportunistic infections in persons with AIDS, and more recently, in organ transplant recipients, patients being treated with immunosuppressive drugs and immunocompetent patients (Weber and Bryan, 1994;Sax et al, 1995;Wanke et al, 1996;Bryan et al, 1997;Raynaud et al, 1998;Gumbo et al, 1999;Wittner and Weiss, 1999;Metge et al, 2000;Lores et al, 2002;Lewis et al, 2003).…”
Section: Overviewmentioning
confidence: 99%
“…Microsporidia cause self-limiting disease in immune-competent individuals; however, in HIV-infected patients and the elderly, it causes progressive infections (8)(9)(10). Symptoms in these high-risk groups can be severe and include chronic diarrhea, encephalitis, keratoconjunctivitis, and hepatitis (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms in these high-risk groups can be severe and include chronic diarrhea, encephalitis, keratoconjunctivitis, and hepatitis (8,9). Incidentally, current drug regimens against this pathogen are only partially effective (8).…”
Section: Introductionmentioning
confidence: 99%
“…Most microsporidial infections have been reported to occur in severely immunocompromised individuals, mainly HIV/ AIDS patients, but cases in HIV-negative people, including travelers and elderly people, are constantly increasing (11,27). Additionally, the number of non-HIV-infected patients with other forms of immunosuppression is also increasing.…”
mentioning
confidence: 99%